2016
DOI: 10.1016/j.ijrefrig.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of a CO2 transcritical refrigeration plant with dedicated mechanical subcooling

Abstract: CO2 transcritical refrigeration cycles require optimization to reach the performance of conventional solutions at high ambient temperatures. Theoretical studies demonstrated that the combination of a transcritical cycle with a mechanical subcooling cycle improves its performance; however, any experimentation with CO2 has been found. This work presents the energy improvements of the use of a mechanical subcooling cycle in combination with a CO2 transcritical refrigeration plant, experimentally. It is tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 18 publications
2
53
0
1
Order By: Relevance
“…The following are samples of the researches which investigate the positive impacts of single modifications; single or multi-ejectors ) (Gullo et al, 2017) (Schönenberger et al, 2014), parallel compression (Javerschek et al, 2015) (Javerschek et al, 2016) , flooded evaporation (Minetto et al, 2014a) (Tambovtsev and Quack, 2007), mechanical sub-cooling (Llopis et al, 2016a) (Bush et al, 2017), evaporative cooling (Girotto and Minetto, 2008) (Lozza et al, 2007), and LT de-superheater (Llopis et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The following are samples of the researches which investigate the positive impacts of single modifications; single or multi-ejectors ) (Gullo et al, 2017) (Schönenberger et al, 2014), parallel compression (Javerschek et al, 2015) (Javerschek et al, 2016) , flooded evaporation (Minetto et al, 2014a) (Tambovtsev and Quack, 2007), mechanical sub-cooling (Llopis et al, 2016a) (Bush et al, 2017), evaporative cooling (Girotto and Minetto, 2008) (Lozza et al, 2007), and LT de-superheater (Llopis et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed the existence of an optimum pressure and, evaluating different subcooling degrees, it was observed that the improvement was greater for the highest subcooling degree (10 K). Later, these results were corroborated experimentally, where increments up to 26.1% in COP and 39.4% in cooling capacity are obtained for 40 • C of heat rejection temperature and an evaporating level of 0 • C [11]. These experiments were optimized in terms of discharge pressure but the subcooling degree was not optimized.…”
mentioning
confidence: 71%
“…Table presents a review of different techniques, their advantages, and limitations in technology adaptation. Nowadays, the modifications in the CO 2 refrigeration cycles are in progress with researcher enhancing the performance with different techniques like single or multiejectors, two‐stage CO 2 compressors, parallel compression, ejectors, MAC applications in automobile industry, flooded evaporation, mechanical subcooling, absorption subcooling, thermoelectric subcooling, evaporative precooling, vortex tube, and expanders to enhance the energy efficiency, COP, and safety.…”
Section: History Of Refrigerantsmentioning
confidence: 99%